Restructuring in L2 Spanish Future-Time Variation: The Evolving Roles of Contextual Sensitivity and Individual Variability in Morphological Development Over Time - Matthew Kanwit (Journal of the European Second Language Association)
A key process during acquisition is restructuring, such as the assignment of new functions to forms with a prior function or the integration of new forms/functions, which can all result in nonlinear development (Bardovi-Harlig, 2017; Ellis & Wulff, 2020). Critically, restructuring also contributes to the notion of multicompetence and subtle morphosyntactic changes for multicompetent language users (Cook, 2020), especially when considering the same language users over multiple data collections (given the dynamic nature of multicompetence) and when considering learner grammars in their own right (rather than compared to those of native speakers; Cook, 1997). This study analyzes 18 intermediate-level learners of Spanish through an oral personal prompt production task over three elicitation periods. Restructuring demonstrated in the reduction in use of an emerging form (i.e., the morphological future) reveals a principled restriction on the form according to temporal distance, consistent with the increased second-language sensitivity to independent linguistic variables documented for numerous structures (e.g., Gudmestad & Geeslin, 2013; Kanwit, 2017). Thus, we consider the notions of U-shaped development and restructuring not only in their typical linkages to overall rates of use but also to the effects of independent (extra)linguistic factors. We aim to demonstrate that restructuring occurs across overall rates of use and the roles of independent predictors, that these changes are revealed over time, and that a study that does not allow for necessary observation over time might miss the opportunity to document such acquisition in progress, potentially underreporting important elements of language users’ evolving multicompetence.